2021
DOI: 10.3390/plants10071306
|View full text |Cite
|
Sign up to set email alerts
|

Pinus Species as Prospective Reserves of Bioactive Compounds with Potential Use in Functional Food—Current State of Knowledge

Abstract: The pine (Pinus L.) is the largest and most heteromorphic plant genus of the pine family (Pinaceae Lindl.), which grows almost exclusively in the northern hemisphere. The demand for plant-based remedies, supplements and functional food is growing worldwide. Although pine-based products are widely available in many parts of the world, they are almost absent as food ingredients. The literature shows the beneficial effects of pine preparations on human health. Despite the wide geographical distribution of pine tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 144 publications
(146 reference statements)
2
30
0
1
Order By: Relevance
“…Pine products are rich in antioxidants. To date, different parts of the trees (bark, needles, shoots, seeds), various extraction methods, and solvents have been used in the studies investigating the antioxidant properties of Pinus trees (Dziedziński et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pine products are rich in antioxidants. To date, different parts of the trees (bark, needles, shoots, seeds), various extraction methods, and solvents have been used in the studies investigating the antioxidant properties of Pinus trees (Dziedziński et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that pine needles would have potent antioxidative activity due to the high phenolic compounds. Dziedziński et al (2021) reported that the total phenolics of alcoholic extract for Pinus brutia tree barks were 412.42 mgGAE g -1 and the aqueous extracts obtained from the shoots of P. sylvestris was 0.86 mgGAE g -1 dry weight basis. It was expressed that the alcoholic extracts have higher total phenolic values than the aqueous extracts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important of them are α-Pinene, δ-3-carene, germacrene-4-ol, and bornyl acetate. The main sesquiterpenes are β-caryophyllene, germacrene D, bicyclogermacrene, δ-cadinene, γ-cadinene, germacrene D-4-ol, cubenol and α-cadinol [4,5]. Research has shown that essential oil exhibits antiparasitic, anti-hyperglycemic, anti-allergenic, anti-viral, anti-spasmodic properties, as well as insecticidal and larvicidal properties [6,7].…”
Section: Introductionmentioning
confidence: 99%